Spatial data modelling for 3D GIS - Abdul-Rahman, Alias (Springer, 2017)
This book covers fundamental aspects of spatial data modelling specifically on the aspect of three-dimensional (3D) modelling and structuring. Realisation of "true" 3D GIS spatial system needs a lot of efforts, and the process is taking place in various research centres and universities in some countries. The development of spatial data modelling for 3D objects is the focus of this book. The book begins with some problems and motivations, the fundamental theories, the implementation, and some applications developed based on the concepts. The book is intended for various geoinformation related professionals like GIS engineers, GIS software developers, photogrammetrists, land surveyors, mapping specialists, researchers, postgraduate students, and lecturers.